2019
DOI: 10.1371/journal.pone.0220263
|View full text |Cite
|
Sign up to set email alerts
|

Enteric and non-enteric adenoviruses associated with acute gastroenteritis in pediatric patients in Thailand, 2011 to 2017

Abstract: Human adenovirus (HAdV) is known to be a common cause of diarrhea in children worldwide. Infection with adenovirus is responsible for 2–10% of diarrheic cases. To increase a better understanding of the prevalence and epidemiology of HAdV infection, a large scale and long-term study was needed. We implemented a multi-year molecular detection and characterization study of HAdV in association with acute gastroenteritis in Chiang Mai, Thailand from 2011 to 2017. Out of 2,312 patients, HAdV was detected in 165 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
71
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 22 publications
30
71
2
3
Order By: Relevance
“…In our study, we noticed that, besides these genotypes, other HAdV genotypes were identified in those presenting with gastrointestinal infection ( Figure 5B), a finding that is similar to what was reported by Kumthip and colleagues. 39 In addition, it is known that specific HAdV species have distinct tissue tropism which may determine the clinical presentation. 40 The presence of HAdV in respiratory tract and stool samples from patients not presenting with any clinical symptoms might be detected incidentally, thus making interpretation of the clinical significance of a positive result difficult.…”
Section: Dovepressmentioning
confidence: 99%
“…In our study, we noticed that, besides these genotypes, other HAdV genotypes were identified in those presenting with gastrointestinal infection ( Figure 5B), a finding that is similar to what was reported by Kumthip and colleagues. 39 In addition, it is known that specific HAdV species have distinct tissue tropism which may determine the clinical presentation. 40 The presence of HAdV in respiratory tract and stool samples from patients not presenting with any clinical symptoms might be detected incidentally, thus making interpretation of the clinical significance of a positive result difficult.…”
Section: Dovepressmentioning
confidence: 99%
“…Epidemiological data indicate that the majority of AdV infections occur in children less than 5 years of age, but AdV epidemics are also common in adults. AdV genotypes 40 and 41 are commonly associated with AGE in pediatric populations worldwide [70][71][72][73][74]. The intestinal tract also appears to be a common site of AdV reactivation under conditions of immunosuppression [75].…”
Section: Virus-virus Co-infection Prevalencementioning
confidence: 99%
“…It can affect infants and immunocompromised individuals, or patients with cardiac and pulmonary diseases [26]. HAdV is currently divided into 9 subgroups (A to I); 90 genotypes have been also recognized [27]. The serotypes causing gastroenteritis are 40-41, which belong to species F and are the most common etiological agents (5-20%) of acute gastroenteritis in young children [28].…”
Section: Human Adenovirus (Hadv)mentioning
confidence: 99%
“…The most common HAdV infection to humans is via the fecal-oral route. Food, particularly contaminated seafoods (shellfish), and water are also vectors of transmission and were also associated with several foodborne outbreaks [27].…”
Section: Human Adenovirus (Hadv)mentioning
confidence: 99%